SERVANT LEADERSHIP AND TEACHER COMMITMENT FOR PASTORAL MANAGEMENT OF CATHOLIC SCHOOLS IN EAST KALIMANTAN - Lorensius Lorensius; Nikolaus Anggal (Program Studi PGSD Universitas Flores, 2026)
Limited empirical research has examined how servant leadership shapes teacher commitment in the management of pastoral activities within Catholic elementary schools. This study aims to analyze the interaction between leadership coordination and teacher commitment in sustaining pastoral management in Catholic schools in East Kalimantan. A qualitative case study design was employed to explore leadership practices and teachers' experiences within their institutional context. Data were collected through in-depth interviews, document analysis, and field observations with 16 informants, comprising three principals and 13 teachers from Catholic elementary schools under the People's Education and Teaching Development Foundation of the Archdiocese of Samarinda. The data were analyzed using reflexive thematic analysis. The findings reveal four interconnected themes: structured coordination in pastoral planning; the affective, normative, and professional commitments of teachers; servant leadership as the core of pastoral management, characterized by empathy, empowerment, and shared responsibility; and adaptive pastoral innovation through the integration of digital practices. These themes demonstrate that servant leadership operates as a moral and managerial framework that strengthens collaboration and organizational coherence in pastoral programs. The study concludes that servant-oriented leadership strengthens teacher commitment and enables Catholic schools to sustain their pastoral identity through participatory, value-driven, and spiritually grounded educational leadership.